Litigation in Medical Practice - Sharma, Anup (Journal of Nepalgunj Medical College, 2025)
Medical litigation occurs when a patient claims harm due to healthcare provider’s negligence to meet the accepted standard of care. These cases often involve allegations of misdiagnosis, surgical errors, medication mistakes, child birth injuries etc. Every patient and their family should be considered as a potential litigant, especially when the health care has been declared as a service industry, which is the foundation of breaking the bond, respect and trust between the doctor and patient.